2011
DOI: 10.1007/s10495-011-0667-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence supporting a role for dihydroorotate dehydrogenase, bioenergetics, and p53 in selective teriflunomide-induced apoptosis in transformed versus normal human keratinocytes

Abstract: We have demonstrated previously that the dihydroorotate dehydrogenase (DHODH) inhibitor teriflunomide (TFN) encourages apoptosis in transformed human keratinocytes. Here we sought to determine if this cytotoxic effect could be restricted to transformed keratinocytes relative to their normal human epidermal keratinocyte (NHEK) counterparts, and ascertain a potential mechanistic basis for the selectivity. The NHEK cells proliferated much slower than the premalignant HaCaT and malignant COLO 16 keratinocytes, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
3
16
2
Order By: Relevance
“…The results are in good agreement with data indicating that the DHODH inhibitor leflunomide/teriflunomide induces apoptosis in a number of human cancer cell lines [10-12]. However, according to [12], transformed keratinocytes with the mutant p53 gene, which lack transcriptionally active p53, are more sensitive to apoptosis induced by teriflunomide than normal keratinocytes with wild-type p53.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The results are in good agreement with data indicating that the DHODH inhibitor leflunomide/teriflunomide induces apoptosis in a number of human cancer cell lines [10-12]. However, according to [12], transformed keratinocytes with the mutant p53 gene, which lack transcriptionally active p53, are more sensitive to apoptosis induced by teriflunomide than normal keratinocytes with wild-type p53.…”
Section: Discussionsupporting
confidence: 86%
“…However, according to [12], transformed keratinocytes with the mutant p53 gene, which lack transcriptionally active p53, are more sensitive to apoptosis induced by teriflunomide than normal keratinocytes with wild-type p53. In normal human epidermal keratinocytes (NHEK) a long-term exposure to teriflunomide was shown to induce cell cycle arrest at Go/G1 due to an induction of the p53 regulated gene CDKN1A encoding the cyclin-dependent kinase inhibitor p21.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the inhibitors of DHODH are currently used for the therapy of autoimmune diseases, and celastrol has long been proved to be very effective for this kind of disease [40]. Furthermore, it was reported that the inhibition of DHODH could induce apoptosis [4143]. Teriflunomide, a well-known specific inhibitor of DHODH, could also induce significant apoptosis of APL cells in our study (Figure 6).…”
Section: Discussionsupporting
confidence: 61%
“…The proapoptotic effect of teriflunomide involves oxidative stress, mitochondrial depolarization and caspase activation [22,23].…”
Section: Introductionmentioning
confidence: 99%